Extremophile Poeciliidae: multivariate insights into the complexity of speciation along replicated ecological gradients - Riesch, R.; Tobler, Michael; Lerp, H.; Jourdan, J.; Doumas, T.; Nosil, P.; Langerhans, R. B.; Plath, M. (My University, 2017)
Background: Replicate population pairs that diverge in response to similar selective regimes allow for an investigation of (a) whether phenotypic traits diverge in a similar and predictable fashion, (b) whether there is gradual variation in phenotypic divergence reflecting variation in the strength of natural selection among populations, (c) whether the extent of this divergence is correlated between multiple character suites (i.e., concerted evolution), and (d) whether gradual variation in phenotypic divergence predicts the degree of reproductive isolation, pointing towards a role for adaptation as a driver of (ecological) speciation. Here, we use poeciliid fishes of the genera Gambusia and Poecilia that have repeatedly evolved extremophile lineages able to tolerate high and sustained levels of toxic hydrogen sulfide (H2S) to answer these questions. Results: We investigated evolutionary divergence in response to H2S in Gambusia spp. (and to a lesser extent Poecilia spp.) using a multivariate approach considering the interplay of life history, body shape, and population genetics (nuclear miscrosatellites to infer population genetic differentiation as a proxy for reproductive isolation). We uncovered both shared and unique patterns of evolution: most extremophile Gambusia predictably evolved larger heads and offspring size, matching a priori predictions for adaptation to sulfidic waters, while variation in adult life histories was idiosyncratic. When investigating patterns for both genera (Gambusia and Poecilia), we found that divergence in offspring-related life histories and body shape were positively correlated across populations, but evidence for individual-level associations between the two character suites was limited, suggesting that genetic linkage, developmental interdependencies, or pleiotropic effects do not explain patterns of concerted evolution. We further found that phenotypic divergence was positively correlated with both environmental H2S-concentration and neutral genetic differentiation (a proxy for gene flow). Conclusions: Our results suggest that higher toxicity exerts stronger selection, and that divergent selection appears to constrain gene flow, supporting a scenario of ecological speciation. Nonetheless, progress toward ecological speciation was variable, partially reflecting variation in the strength of divergent selection, highlighting the complexity of selective regimes even in natural systems that are seemingly governed by a single, strong selective agent.
Citation: Riesch, R., Tobler, M., Lerp, H., Jourdan, J., Doumas, T., Nosil, P., . . . Plath, M. (2016). Extremophile Poeciliidae: multivariate insights into the complexity of speciation along replicated ecological gradients. Bmc Evolutionary Biology, 16, 15. doi:10.1186/s12862-016-0705-1
Keywords: Hydrogen Sulfide; Gambusia; Ecological Speciation; Life-History; Evolution; Morphometrics